Crop Ontology new web site using a graph database - CGIAR Platform for Big Data in Agriculture (2021)
The graph based web site was publicly released in November after a round of user tests. This web site is used by a group of 32 curators to publish crop specific ontologies. The new web site provides improved curation and display features.